THE EFFECTIVENESS OF THE PROSPEROUS RICE SOCIAL ASSISTANCE IMPLEMENTATION PROGRAM (BANSOS RASTRA) ON FOOD SECURITY IN TANJUNG PURA DISTRICT, LANGKAT REGENCY. - Nurmauliza Nurmauliza; Roswota Afni (Proceeding International Seminar of Islamic Studies, 2022)
Food security is the availability of food and the ability of a person to access it. A household is said to have food security if the occupants are not in a state of hunger or are haunted by the threat of hunger. The Rastra Social Assistance Program is part of the National Food Security system, which is carried out in a series of efforts to achieve food independence and sovereignty. The Indonesian government gives great priority to national food security policies, this is because the majority of Indonesia's population consumes rice as the main food so that rice is a very strategic national commodity, the goals and objectives of this program are to reduce expenditure burdens and be able to meet some of the basic needs food for the poor. Tanjung Pura District with a population of 68,464 people and a population of Langkat Regency reached 1,028,309 million people in 2017 and 6,863 families receiving the benefits of Social Assistance Rastra. This analysis uses descriptive qualitative data with survey data types. Then a sample of 44 participants received Rastra Social Assistance was taken. The sampling technique in this study used incidental sampling techniques. Based on the results of research conducted in Tanjung Pura District, the Social Assistance Rastra program aimed at the poor has been effective in helping to reduce the expenditure burden on beneficiary families and increasing family food security.